Fish Cell Spheroids, a Promising In Vitro Model to Mimic In Vivo Research: A Review - Antonio Gómez-Mercader; Luis Monzón-Atienza; Daniel Montero; Jimena Bravo; Félix Acosta (Cells)
In vitro cell culture systems serve as instrumental platforms for probing biological phenomena and elucidating intricate cellular mechanisms. These systems afford researchers the opportunity to scrutinize cellular responses within a regulated environment, thereby circumventing the ethical and logistical challenges associated with in vivo experimentation. Three-dimensional (3D) cell cultures have emerged as a viable alternative to mimic in vivo environments. Within this context, spheroids are recognized as one of the most straightforward and efficacious models, presenting a promising substitute for conventional monolayer cultures. The application of 3D cultures of fish cells remains limited, focusing mainly on physiological and morphological characterization studies. However, given the capacity of spheroids to emulate in vivo conditions, researchers are exploring diverse applications of these 3D cultures. These include eco-toxicology, immunology, drug screening, endocrinology, and metabolism studies, employing a variety of cell types such as fibroblasts, hepatocytes, embryonic cells, gonadal cells, gastrointestinal cells, and pituitary cells. This review provides a succinct overview, concentrating on the most frequently employed methods for generating fish cell spheroids and their applications to date. The aim is to compile and highlight the significant contributions of these methods to the field and their potential for future research.